Food security in Indonesia: the role of social capital. Issue 1 (31st December 2023) - Rusmawati, Estiana; Hartono, Djoni; Aritenang, Adiwan Fahlan
ABSTRACT: Social capital (i.e. bonding and bridging) affects food security. In Indonesia, studies have been conducted at the site level, covering households in specific provinces, districts, subdistricts, or even villages. Accordingly, this study contributes to the existing literature by employing a sample of 68, 304 households across Indonesia using data from Statistics Indonesia's (BPS's) 2018 National Socioeconomic Survey (SUSENAS). Based on Lewbel's (2012. "Using Heteroscedasticity to Identify and Estimate Mismeasured and Endogenous Regressor Models." Journal of Business and Economic Statistics 30 (1): 67–80) two-stage least squares (2SLS) regression test, the results suggest that bonding and bridging social capital positively affect food security. Specifically, bridging social capital has a more substantial influence on food security.